Expression of transforming growth factor-beta 1 is increased in human vascular restenosis lesions. - Nikol, S; Isner, J M; Pickering, J G; Kearney, M; Leclerc, G; Weir, L (The Journal of Clinical Investigation, 1992)
Human atheromata obtained in vivo were used to test the hypothesis that transforming growth factor-beta 1 plays a role in the development of vascular restenosis. We analyzed 28 specimens from patients with primary atherosclerotic or restenotic lesions; 26 of these were obtained by directional atherectomy and 2 at the time of coronary bypass surgery. Seven control tissues included operatively excised segments of human internal mammary artery, myocardium, and unused portions of vein graft obtained intraoperatively. From these 35 specimens, 210 sections were examined using in situ hybridization. Measurement of silver grains/nucleus disclosed that expression of transforming growth factor-beta 1 mRNA was highest in restenotic tissues (P < 0.001 vs. primary atherosclerotic tissues) and lowest in nonatherosclerotic (control) tissues. In cultures of human vascular smooth muscle cells grown from explants of internal mammary artery, expression of mRNA for transforming growth factor-beta 1 was significantly greater in subconfluent than in confluent smooth muscle cells (P = 0.05). Transforming growth factor type-beta III receptor was expressed in cell cultures and undetectable in the tissue specimens. Sections taken adjacent to those studied by in situ hybridization were examined by immunohistochemistry using antibodies against transforming growth factor-beta 1 and alpha-actin (as a marker for smooth muscle cells) and disclosed transforming growth factor-beta 1 in smooth muscle cells present in these sections. These findings are consistent with the concept that transforming growth factor-beta 1 plays an important role in modulating repair of vascular injury, including restenosis, after balloon angioplasty. Images